Experiences of parents of children with disabilities whose children dropped out of school - Alcazaren, Anton Jose A. (Animo Repository, 2016)
This study explored the factors that led to the dropping out of special children according to their parents including the parents experiences prior to making the decision of making their children drop out. In the Philippines, there are 1.2 million out of school children (UNESCO, 2015). This study used a quantitative-qualitative research design. Parents were surveyed about the factors that led to their children's dropping out of school such as attitudinal, financial, physical-environmental, and other kinds of dropout factors as well as their human rights awareness. From a total of 86 parents, 30 were selected for interviews to supplement the surveys. Results showed that financial factors specifically: poverty, inconsistent family monthly income, lack of funds for other school costs, and budget are mostly spent for necessities registered as minor dropout factors and were considered causes of dropping out. Results also showed a negative correlation between financial dropout factors and parents rights awareness levels. Interviews with parents also revealed a different set of dropout factors which included forms of disabilities in relation to their children's educational program, their children showing forms of school disengagement behavior, children's medical condition, and teacher experiences or child-teacher relationship. Overall, the parents acknowledged in the interviews that their experiences prior to deciding their children would drop out were quite negative.